Transferable antibiotic resistance plasmids from biogas plant digestates often belong to the IncP-1ε subgroup - Wolters, Birgit; Kyselková, Martina; Krögerrecklenfort, Ellen; Kreuzig, Robert; Smalla, Kornelia (Frontiers in Microbiology, 2015)
Manure is known to contain residues of antibiotics administered to farm animals as well as bacteria carrying antibiotic resistance genes (ARGs). These genes are often located on mobile genetic elements. In biogas plants (BGPs), organic substrates such as manure and plant material are mixed and fermented in order to provide energy, and resulting digestates are used for soil fertilization. The fate of plasmid carrying bacteria from manure during the fermentation process is unknown. The present study focused on transferable antibiotic resistance plasmids from digestates of seven BGPs, using manure as a co-substrate, and their phenotypic and genotypic characterization. Plasmids conferring resistance to either tetracycline or sulfadiazine were captured by means of exogenous plasmid isolation from digestates into Pseudomonas putida KT2442 and Escherichia coli CV601 recipients, at transfer frequencies ranging from 10-5 to 10-7. Transconjugants (n = 101) were screened by PCR-Southern blot hybridization and real-time PCR for the presence of IncP-1, IncP-1ε, IncW, IncN, IncP-7, IncP-9, LowGC and IncQ plasmids. While 61 plasmids remained unassigned, 40 plasmids belonged to the IncP-1ε subgroup. All these IncP-1ε plasmids were shown to harbor the genes tetA, sul1, qacE∆1, intI1 and integron gene cassette amplicons of different size. Further analysis of 16 representative IncP-1ε plasmids showed that they conferred six different multiple antibiotic resistance patterns and their diversity seemed to be driven by the gene cassette arrays. IncP-1ε plasmids displaying similar restriction and antibiotic resistance patterns were captured from different BGPs, suggesting that they may be typical for this environment. Our study showed that BGP digestates are a potential source of transferable antibiotic resistance plasmids and in particular the broad host range IncP-1ε plasmids might contribute to the spread of ARGs when digestates are used as fertilizer.